2009
DOI: 10.1521/aeap.2009.21.3_supp.81
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1Genotype Modifies the Impact of Smoking on Effectiveness of HAART Among Women

Abstract: We have recently shown that cigarette smoking is associated with lesser responses to potent antiretroviral therapies. Certain Cytochrome P-450 enzymes activate compounds derived from tobacco smoke into toxic forms that may promote HIV-1 gene expression through promotion of DNAadduct formation by the oxidation of chemical constituents of cigarette smoke, such as polyaromatic hydrocarbons and dioxins. To explore the association between environmental and genetic factors to viral replication in women who smoke and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
2
23
0
2
Order By: Relevance
“…In the current sample, smokers were more likely than non-smokers to have a detectable viral load. This finding expands upon previous research suggesting that smokers experience virologic failure sooner than non-smokers [20]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current sample, smokers were more likely than non-smokers to have a detectable viral load. This finding expands upon previous research suggesting that smokers experience virologic failure sooner than non-smokers [20]. …”
Section: Discussionsupporting
confidence: 88%
“…This biological pathway is supported by previous studies that have found that smokers had poorer viral and immunologic response to antiretroviral therapy, a greater risk of virologic rebound, and more frequent immunologic failure compared to non-smokers [19]. More recently, Feldman and colleagues [20] found that the adverse effects of smoking on medication response remained even after controlling for adherence. Thus, it is plausible that smoking may contribute to a biological vulnerability that increases susceptibility to co-morbid medical conditions and dampens the therapeutic effect of HIV medications, independent of the relationship with adherence.…”
Section: Discussionsupporting
confidence: 57%
“…Notwithstanding the counteracting immunosuppressive effect of HIV/smoking on the efficacy of therapy, other possible causes of smoking-related interference with HAART include 1) smoking is a surrogate marker of a noncompliant disposition [81,82]; 2) higher frequencies of side-effects in smokers, including neuropsychiatric symptoms associated with efavirenz-based HAART regimens [83]; 3) negative effects of smoking-related activation of cytochrome P450 enzymes, such as the CPY1A1-m1 variant, which promote oxidative conversion of smoke-derived toxicants to DNA adducts, causing activation of genes that support HIV replication [70,84]; 4) altered pharmacokinetics of antiretroviral agents, possibly related to smoking-mediated induction of CYP3A4 and aryl-hydrocarbon-hydroxylases [85,86], which metabolise many protease and non-nucleoside reverse transcriptase inhibitors [87,88]; and 5) smoking-induced mitochondrial oxidative stress [89], which may exacerbate the adverse effects of antiretroviral drugs that induce mitochondrial toxicity, such as drugs from the nucleoside reverse transcriptase inhibitor class [90].…”
Section: Effects Of Smoking On Hiv Disease Progression and Treatmentmentioning
confidence: 99%
“…For example, CYP1A1 is not directly involved in the inactivation of antiretrovirals, however, the CYP1A1 genotype was reported to impact the treatment outcome of highly active antiretroviral therapy (HAART) among female smokers. 30 The genotype with higher activity is associated with impaired HAART effectiveness. Since this enzyme could convert smoke-derived compounds to DNA-damaging agents that promote HIV-1 gene expression and replication, the proposed explanation is that higher CYP1A1 activity contributes to a higher concentration of DNA-damaging agents in HIV-infected tissues.…”
mentioning
confidence: 99%
“…Since this enzyme could convert smoke-derived compounds to DNA-damaging agents that promote HIV-1 gene expression and replication, the proposed explanation is that higher CYP1A1 activity contributes to a higher concentration of DNA-damaging agents in HIV-infected tissues. 30 Whether the cervicovaginal CYP1A1 could impact the microbicide efficacy among female smokers would be an interesting topic for future research.…”
mentioning
confidence: 99%